Diversity of microfungi in decaying vegetable wastes in Manipur, North-East India - R.R. PANDEY, G. SHARMA* and (Indian Phytopathology, 2012)
The microfungal assemblages of seven different types of vegetable wastes, viz., peels of Euryale ferox, Phaseolus sp., Solanum tuberosum, Sechiumedule, petioles of Brassica oleracea, pseudostem of Musa paradisiaca and sheaths of young edible shoots of Bambusa arundinaceae were studied during 8 months of decomposition period (November, 2008 to July, 2009) in nylon mesh bags kept on field soil surface and in experimental pots individually as well as with the composite mixture of all the vegetable types in equal proportions. A total of 78 micro fungi belonging to 26 genera including 4 sterile mycelia and one unidentified form were isolated, out of which 40 were specifically isolated from litter bags, 13 species from pots and 23 species were common to both experimental types. Aspergillus niger and Fusarium oxysporum were the most dominant fungi occurring in all the 8 test samples with average frequency of occurrence as high as 54.31 & 54.56% for A. niger and 55.13 & 51.88% for F. oxysporum recovered from litter bag and pot experiments respectively. Other ubiquitous fungi were Aspergillus flavus, Chaetomium globossum, Cladosporium cladosporioides, Gliocladium fimbriatum, Paecilomyces variotii, Rhizopus nigricans, sterile white mycelia, Trichoderma longibrachiatum and T. virens that occurred in 4 or more decaying vegetable wastes samples in both experimental conditions. High Shannon Diversity index (H′) of microfungi among the 8 study samples was recorded.